Pity beetle algorithm – A new metaheuristic inspired by the behavior of bark beetles. (July 2018) - Kallioras, Nikos Ath.; Lagaros, Nikos D.; Avtzis, Dimitrios N.
Highlights: A new metaheuristic algorithm (PBA) is presented along with its efficiency against state-of-the-art algorithms. PBA was compared to well established metaheuristic algorithms. PBA performance was assessed with the CEC 2014 benchmark and complexity tests. Abstract: In the past years a great variety of nature-inspired algorithms have proven their ability to efficiently handle combinatorial optimization problems ranging from design and form finding problems to mainstream economic theory and medical diagnosis. In this study, a new metaheuristic algorithm called Pity Beetle Algorithm (PBA) is presented and its efficiency against state-of-the-art algorithms is assessed. The proposed algorithm was inspired by the aggregation behavior, searching for nest and food, of the beetle named Pityogenes chalcographus, also known as six-toothed spruce bark beetle. This beetle has the ability to locate and harvest on the bark of weakened trees into a forest, while when its population exceeds a specific threshold it can infest healthy and robust trees as well. As it was proved in this study, PBA can be applied to NP-hard optimization problems regardless of the scale, since PBA has the ability to search for possible solutions into large spaces and to find the global optimum solution overcoming local optima. In this work, PBA was applied to well-known benchmark uni-modal and multi-modal, separable and non-separable unconstrained test functions while it was also compared to other well established metaheuristic algorithms implementing also the CEC 2014 benchmark and complexity evaluation tests.